Selecting air speeds for cooling at sedentary and non-sedentary office activity levels. (September 2017) - Zhai, Yongchao; Arens, Edward; Elsworth, Kit; Zhang, Hui
Abstract: Subjects were tested under a set of air speed setpoints as might be used in automated control of ceiling fans. At lower temperatures the fan speeds were slightly higher than needed for thermal neutrality, to account for occasional non-sedentary metabolic rates associated with getting up, standing, or moving about. At higher temperatures the air speed supplied was conservative, to minimize mechanical wind disruption, while allowing thermal sensations above neutral. Twenty-three subjects in summer clothing experienced a matrix of four temperatures (24 °C, 26 °C, 28 °C and 30 °C), two levels of humidity (RH 40% and 60%), and two metabolic rate (1.0, 1.4 met). Each test condition was 2 h in length, made up of four 30-min sessions following the same pattern: sedentary without fan; sedentary under a fixed fan speed chosen by experimenters to be appropriate for the temperature; exercising at 1.4 met under personally adjusted fan speed; and sedentary under personally adjusted fan speed. Throughout, the subjects rated their thermal sensation, thermal comfort, perceived air quality, and air-movement acceptability and preference. The air speeds personally chosen by test subjects in the 24 °C and 26 °C conditions differed little from the experiment's fixed air speeds. Subjects chose significantly greater air speeds in the 28 °C and 30 °C conditions. The elevated 1.4 metabolic rate slightly increased subjects' thermal sensation, but caused no significant difference in the air speeds they chose for sedentary activity. Personal control over air movement had no significant effect on comfort in the conditions tested. Highlights: A range of air movement improves thermal comfort and PAQ in warm environments. A single set of air speeds can provide comfort for both 1.0 and 1.4 met levels. Availability of air movement is more important than providing control over it in warm temperatures.